Synergistic Magnetic Field-Photocatalysis for the Concurrent Removal of Inorganic and Organic Contaminants over Prfeo3/Zno Heterostructures - Casagrande-Denardin, J (Elsevier B.V., 2023)
Improving the photocatalytic detoxifying performance of the existing photocatalysts via external fields is one of the effective alternative ways. Herein, we synthesized the PrFeO3 (PFO), ZnO, and PrFeO3/ZnO (PFO/ZnO) p-n heterostructure photocatalyst in situ through a simple hydrothermal method and demonstrated the impact of magnetic field (MF) on the simultaneous removal of inorganic Cr (VI) and organic pollutant phenol red (PR). The prepared photocatalysts were systematically characterized by various techniques including the FE-SEM, TEM, XRD, DRS, and VSM for their morphology, size, structural, optical, and magnetic properties. The PFO/ZnO nanocomposite demonstrated conspicuously enhanced photocatalytic activity towards the decompositions of the contaminants in comparison with their pure PFO and ZnO nanostructures owing to the effective electron/hole pairs separation by forming a hetero-junction structure. Significantly, high removal efficiencies (Cr (VI): 96.4 % and PR: 99.6%) were achieved by the PFO/ZnO nanocomposites for the concurrent decomposition of assorted (Cr (VI) or/and PR) pollutants by imposing the 0.5 T of an external magnetic field. The highest rate constant values (0.081 min−1 for Cr (VI) and 0.123 min−1 for PR) for removing the assorted pollutants were calculated for PFO/ZnO photocatalyst which is 2.5 and 2.7 times higher than individual pollutant removal under the same magnetic field condition. The excellent catalytic performance of PFO/ZnO is ascribed to the magnetic field-induced synergistic effect of high-rate photoinduced charge carrier separation and transfer through the interface of PFO/ZnO. Moreover, the PFO/ZnO catalyst also exhibited good reusability, stability and achieved reproducibility in MF-assisted catalytic systems. The finding in this work may concede new insight for improving the photocatalytic performance in an external MF by designing semiconductor architectures. © 2023 Elsevier B.V.